Epidemic malaria in the Menoreh Hills of Central Java. - Barcus, M; Laihad, F; Sururi, M; Sismadi, P; Marwoto, H; Bangs, M; Baird, J (2002)
After more than 50 years of effective management, resurgent malaria threatens residents in the Menoreh Hills and the foothills of the Dieng Plateau of Central Java, Indonesia. The Dieng Plateau dominates the highland center of Central Java. The steep Menoreh Hills, surrounded by rice paddy habitats, cover approximately 500 km2 with no peaks greater than 1,000 m. We studied epidemic malaria in Purworejo district, one of the three districts containing the Menoreh Hills. Between 1986 and 1995, the annual parasite incidence (API) in Purworejo ranged from 2 to 11 cases per 1,000 residents per year and was typically approximately 5 per 1,000. In 2000 the API was 44.5. This sharp increase was confined to subdistricts in and around the Menoreh Hills and Dieng Plateau foothills. The primary vectors of malaria, those favoring steep, forested hillsides on Java, were Anopheles maculatus and Anopheles balabacensis. Deterioration of vector control activity, followed by a severe economic downturn in 1997, may explain the epidemic. Malaria in the Menoreh Hills and lower Dieng Plateau threatens surrounding areas of rice paddy inhabited by Anopheles aconitus as well as a nearby coastal habitat where the even more efficient vector Anopheles sundaicus occurs in abundance. Most of the 130 million people living on Java never experienced the hyper- and holoendemic malaria that occurred throughout most of the island before the effective DDT spraying and chloroquine treatment campaigns of the 1950s. Reintroduced endemic malaria threatens the island of Java.